Safety Evaluation of Prolonged Administration of Stresroak® in Grower Cockerels - Oyagbemi, A.A.; Saba, A.B.; Arowolo, R.O.A. (International Journal of Poultry Science, 2008)
Stresroak® is a herbal preparation from combination of Phyllatus emblica, Ocimum sanctum, Withania, somnifera, Mangefira indica and Shilajit species. The Ayurvedic drug is used as anti-stress, immunomodulator, adaptogen and performance enhancer in poultry management. with outstanding results. The toxicological effects of prolonged administration of Stresroak in grower Cockerels was evaluated using haematological parameters and serum biochemical assay. Sixty growing Cockerels were used in this study. The birds were randomly but equally divided into 5 groups. Birds in groups A, B, C and D were administered with 109.8mg 292.8mg, 585.6mg and 951.6mg of the drug dissolved in 2 litres of distilled water, daily for 60 days respectively. While the dose of group A was recommended by the drug manufacturer, the birds in group E were administered with 0.9% Physiological saline. The haematological parameters analyzed were total red blood cell (RBC) count, total white blood cell (WBC) count, haemoglobin concentration (Hb), platelets count and heterophil/lymphocytes ratio. Plasma enzymes and proteins analyzed were total proteins (T.P), albumin (ALB), globulin (GLO), fibrinogen (FIB), total bilirubin (T.Bil), alkaline phosphatase (ALP), aspartate aminotransferase (AST), alanine Aminotransferase (ALT) and gamma glutamyltransferase (GGT). Stresroak generally improved haematological parameters in chicken administered with the drug when compared with the chicken in the control group. The significant (P< 0.05) increase in total RBC and WBC counts and MCH both at 30 and 60 days post-administration especially for the therapeutic dose, show that Stresroak® probably enhances erythropoiesis. Lower heterophil/lymphocyte ratio was observed for the groups that received the highest doses of Stresroak® and this was consistent throughout the course of the experiment, which implies that the herbal preparation improved the immunity of the chicken. The plasma levels of total protein, globulin, albumin and fibrinogen increased dose-dependently both at 30 and 60 days post- Stresroak® administration. The plasma levels of ALP and AST were significantly lowered while non-significant changes were observed for plasma levels of ALT and GGT at 30 days post- Stresroak® administration. Conversely, by 60 days post- Stresroak® administration, the plasma levels of ALT and GGT were significantly (P< 0.05) elevated except in cockerels in group A that received the recommended therapeutic dosage; where the plasma levels was observed to be lower for ALP (P< 0.05) and AST (P>0.05). Histopathological findings did not however reveal any damage to the liver or kidney. It was concluded that Stresroak® exhibits haematinic, hepato-protective and immune stimulation properties and is safest at its recommended therapeutic dose as it was found to have potential tendency to cause hepatic injury when administered for longer period and at higher dosages.